Depletion of perivascular macrophages delays ALS disease progression by ameliorating blood-spinal cord barrier impairment in SOD1G93A mice - Adachi, Kazuki; Miyata, Kota; Chida, Yukino; Hirose, Mikako; Morisaki, Yuta; Yamanaka, Koji; Misawa, Hidemi (Frontiers in Cellular Neuroscience, 2023)
Amyotrophic lateral sclerosis (ALS) is a fatal motor neuron disease in which non-cell-autonomous processes have been proposed as its cause. Non-neuronal cells that constitute the environment around motor neurons are known to mediate the pathogenesis of ALS. Perivascular macrophages (PVM) are immune cells that reside between the blood vessels of the central nervous system and the brain parenchyma; PVM are components of the neurovascular unit and regulate the integrity of the bloodspinal cord barrier (BSCB). However, it is not known whether regulation of BSCB function by PVM is involved in the pathogenesis of ALS. Here, we used SOD1 G93A mice to investigate whether PVM is involved in the pathogenesis of ALS. Immunostaining revealed that the number of PVM was increased during the disease progression of ALS in the spinal cord. We also found that both antiinflammatory Lyve1 + PVM and pro-inflammatory MHCII + PVM subtypes were increased in SOD1 G93A mice, and that subtype heterogeneity was shifted toward MHCII + PVM compared to WT mice. Then we depleted PVM selectively and continuously in SOD1 G93A mice by repeated injection of clodronate liposomes into the cerebrospinal fluid and assessed motor neuron number, neurological score, and survival. Results showed that PVM depletion prevented the loss of motoneurons, slowed disease progression, and prolonged survival. Further histological analysis showed that PVM depletion prevents BSCB collapse by ameliorating the reduction of extracellular matrix proteins necessary for the maintenance of barrier function. These results indicate that PVM are involved in the pathogenesis of ALS, as PVM degrades the extracellular matrix and reduces BSCB function, which may affect motor neuron loss and disease progression. Targeting PVM interventions may represent a novel ALS therapeutic strategy.